Origami fun: buildings - Leaf, Christina (2021)
"Information accompanies step-by-step instructions on how to fold origami buildings. The text level and subject matter are intended for students in grades 3 through 8"--
Empire State Building -- Sydney Opera House -- Sagrada Familia -- Chureito Pagoda -- Eiffel Tower -- Chichen Itza -- Taj Mahal.
Includes bibliographical references and index.
Ages 7-13
Grades 4-6
Keywords: Origami -- Juvenile literature; Buildings -- Juvenile literature